A Winning Framework for Public-Private Partnerships : Lessons from 60-plus IFC Projects - Florizone, Richard; Carter, Laurence (International Finance Corporation, Washington, DC, 2014)
Despite global financial uncertainty and increased public mistrust of business, partnerships between the public and private sectors have continued to grow- driven by governments' need to access external financing and expertise, by the private sector's search for new opportunities, and by governments' desire to grow the private sector. This report addresses the critical question: how can the public and private sectors build successful partnerships?